Removal of Fibromatous Epulis Around The Anterior Maxillary Teeth (Case Report) - Siti Sopiatin; Ina Hendiani; Ira Komara; Prajna Metta; Budhi Cahya Prasetyo; Chandra Andi Bawono (FKG Universitas Syiah Kuala, 2023)
Fibromatous epulis is one of the most common features of the gingival enlargement. This condition results from inflammation of the gingiva, leading to fibrotic overgrowth caused by local or systemic factors. These enlargements increase gingival pocket depth, which may lead to periodontal disease causing functional disturbances in mastication, altered speech, aesthetics, and even psychological problems. A- 42-year-old male patient with gingival fibrotic overgrowth known as fibromatous epulis on proximal teeth in the middle upper front region extended to the palatal and accompanied by slight pain. The clinical appearance of this lesion was firm, slightly soft, and fibrotic, with 6 mm probing depth and bleeding on gingival probing at the proximal of 11 and 21 teeth region. In this case, periodontal surgery to eliminate gingival enlargement was a gingivectomy under local anaesthesia. The fibromatous epulis was entirely eliminated by gingivectomy, also effectively treated the inflammation, facilitated oral prophylaxis procedure, and increased the aesthetics.